The Principles of Fraud under the Law of the Contract in Pakistan: An Overview (PAKISTAN JOURNAL OF LAW, ANALYSIS AND WISDOM, 2024)
This article critically evaluates the jurisprudence surrounding fraud under the law of contract in Pakistan. It analyses the judgements of the Pakistani superior courts and the jurisprudence enunciated therein. It deliberates upon the meaning of fraud, on whom the onus to prove fraud lies upon. Whether the law provides for any limitation against a claim for a contract that is hit by fraud. The main findings of this paper are that fraud is an intentional act of deception committed through words or conduct to not just deceptively gain the consent of another party but also to deliberately injure him. The courts have deliberated upon this by either relying on either Pakistani law or foreign judicial decisions or law dictionaries. The onus to prove fraud is on the ones who allege it. A claim of fraud in a contract has a time-period of three years from the time the alleged fraud came within their notice. The victim has two remedies to choose from, either he can declare the contract to be null and void and thus make it of no legal effect. Or if he believes that he will benefit from the contract, he can have it enforced instead. In other words, a contract hit by fraud is voidable on the option of the wronged party. However, if there was a possibility that the party was able to discover the fraud by exercising due diligence like an ordinary man, then the contract will not be voidable. The courts also incorrectly declare contracts involving fraud to be void when in reality, it is voidable at the option of the wronged party. The methodology used in this paper is doctrinal.